Blockchain-based decentralised access control scheme for dynamic hierarchies. (8th November 2021) - Pareek, Gaurav; Purushothama, B.R.
Cryptographic hierarchical access control is widely employed in systems that manage data or resources. To meet scalability and high availability requirements, it is desirable that an access control scheme is decentralised in nature. Proposing a blockchain-based cryptographically decentralised access control scheme for dynamic hierarchies that is consistent with the standard centralised hierarchical access control model is the main focus of this paper. We use blockchain transactions, consensus and validation mechanisms as tools to achieve cryptographic decentralisation of hierarchical access control. Important highlight of the paper is that the proposed decentralised scheme does not compromise on performance and storage requirements of the standard centralised hierarchical key assignment schemes. In particular, the proposed scheme requires symmetric decryption operations for key derivation, is secure under strong key indistinguishability and features efficient dynamic update operations without any trusted third-party. Proposed is the first hierarchical key assignment scheme that features all the aforementioned properties.